ANTIOXIDANT ACTIVITY OF ROASTED KEDAWUNG SEED (Parkia timoriana) USING SCAVENGER FREE RADICAL DPPH METHOD - Ismanurrahman Hadi; Teguh Adiyas Putra; Reza Alrayan; Arif Setiawansyah; Dewi Luthfiana; Perdana Priya Haresmita (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Kedawung seeds (Parkia timoriana) contain polyphenolics and flavonoids that can provide pharmacological activities, such as antioxidants. In several regions of Indonesia, kedawung seeds are preserved using the roasting method. This study aimed to analyze the effect of roasting on the content of phytochemical compounds and determine their antioxidant activity using the DPPH method. Roasted kedawung seeds were extracted using a maceration method in ethanol. Phytochemical screening was performed to qualitatively analyze the contents of several phytochemical compounds in the extract. The results showed that roasted kedawung seed extract contained alkaloids, flavonoids, saponins, and terpenoids. Antioxidant testing was performed using the DPPH method with ascorbic acid as a positive control. The IC50 value of ascorbic acid, P. timoriana seed and roasted seed of P. timoriana measured each 12.3 ppm; 20.6 ppm and 9.8 ppm; which categorized as strong antioxidant compounds. These results indicated an increase in the antioxidant effect after roasted seed processing. It concluded that the roasting process could enhance antioxidant effect of P. timoriana seed Keywords: Kedawung seeds, roasted method, antioxidant, DPPH